2018
DOI: 10.3389/fpubh.2018.00085
|View full text |Cite
|
Sign up to set email alerts
|

Immune-Modulating Perspectives for Low Frequency Electromagnetic Fields in Innate Immunity

Abstract: In recent years, the effects of electromagnetic fields (EMFs) on the immune system have received a considerable interest, not only to investigate possible negative health impact but also to explore the possibility to favorably modulate immune responses. To generate beneficial responses, the immune system should eradicate pathogens while “respecting” the organism and tolerating irrelevant antigens. According to the current view, damage-associated molecules released by infected or injured cells, or secreted by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 115 publications
0
31
0
1
Order By: Relevance
“…These signaling mechanisms are important to the subsequent activation of homeostatic mechanisms that control the immune response in pro-and anti-inflammatory reactions that allow for therapeutic treatments. 9 In this review, we described the effects of PEMF on inflammatory/immune regulators and transcription factors relevant to the activation of danger signals and innate immune cells. Achieving homeostasis in the face of acute inflammatory/immune challenges in the human body involves maintaining a balance of highly complex biochemical and cellular interactions, such as cytokine expression and signal transduction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These signaling mechanisms are important to the subsequent activation of homeostatic mechanisms that control the immune response in pro-and anti-inflammatory reactions that allow for therapeutic treatments. 9 In this review, we described the effects of PEMF on inflammatory/immune regulators and transcription factors relevant to the activation of danger signals and innate immune cells. Achieving homeostasis in the face of acute inflammatory/immune challenges in the human body involves maintaining a balance of highly complex biochemical and cellular interactions, such as cytokine expression and signal transduction.…”
Section: Resultsmentioning
confidence: 99%
“…Using PEMF to regulate cell signaling mechanisms involved in the inflammatory/immune response pathways of different cell types has become an innovative alternative treatment in the pursuit of regenerative therapies. 9,10 Several studies have reported that PEMF can modulate both cell surface receptor expression/activation and downstream signal transduction pathways, thereby restoring homeostatic cell functions such as viability, proliferation, differentiation, communication with neighboring cells, and interaction with components of the extracellular matrix (ECM). [11][12][13][14][15][16][17][18] PEMF can activate multiple intracellular pathways, including numerous processes and biochemical mechanisms within both the immune system and tissue regenerative processes, such as the musculoskeletal system 7,19,20 and the nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of ELF-EMFs on biological systems such as immune cells have received extensive interest. Other than the possible negative health impacts, the possibility of ELF-EMFs to favorably modulate immune responses has also been evaluated [ 14 ]. Studies have been consistent in stating that the effects of ELF-EMFs vary with frequency, amplitude, and duration of exposure, as well as with the characteristics of the cell types.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of the living organisms and EMF can occur via changes the activation of the channel and pumps in the cell membrane, so the cell ionic balance is rearranged [6]. EMF changes cell function via mainly oxidative stress biochemical cascades, intense apoptosis and other vital properties [7,8]. Reactive oxygen species (ROS) occurs in oxidative reactions to produce energy in metabolic and physiological processes in the organism.…”
Section: Discussionmentioning
confidence: 99%